2012
DOI: 10.1016/j.expneurol.2012.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Low nigrostriatal reserve for motor parkinsonism in nonhuman primates

Abstract: Objective Nigrostriatal reserve refers to the threshold of neuronal injury to dopaminergic cell bodies and their terminal fields required to produce parkinsonian motor deficits. Inferential studies have estimated striatal dopamine reserve to be at least 70%. Knowledge of this threshold is critical for planning interventions to prevent symptom onset or reverse nigrostriatal injury sufficient to restore function in people with Parkinson disease. In this study, we determine the nigrostriatal reserve in a non-huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
80
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 37 publications
(91 citation statements)
references
References 36 publications
9
80
2
Order By: Relevance
“…Two postmortem studies using more rigorous quantitative methods, such as using a tessellation method [17] and dissector-based neuromorphometry [27], found that about 30% of nigral neuronal loss appeared sufficient to cause motor symptoms in PD [2]. However, recent research suggests that the first symptoms of Parkinson's disease may manifest after just a 20% decrease in the number of dopaminergic neurons SNc, which has been shown in animal models where a reduction of about 14 to 23% of nigral neuron count or 14% to 37% of striatal dopamine was sufficient to induce mild parkinsonism [43].…”
Section: Discussionmentioning
confidence: 99%
“…Two postmortem studies using more rigorous quantitative methods, such as using a tessellation method [17] and dissector-based neuromorphometry [27], found that about 30% of nigral neuronal loss appeared sufficient to cause motor symptoms in PD [2]. However, recent research suggests that the first symptoms of Parkinson's disease may manifest after just a 20% decrease in the number of dopaminergic neurons SNc, which has been shown in animal models where a reduction of about 14 to 23% of nigral neuron count or 14% to 37% of striatal dopamine was sufficient to induce mild parkinsonism [43].…”
Section: Discussionmentioning
confidence: 99%
“…Some investigations have indicated that motor symptoms appear when there has been loss of approximately 30% of substantia nigra dopamine neurons or 50 to 70% of nigrostriatal dopaminergic axonal terminals in the striatum, although other studies have suggested that motor symptoms may appear with more preservation of dopamine neurons and striatal dopamine terminals than previously understood (Burke & O’Malley, 2013; Tabbal et al, 2012). Further, although Braak staging has drawn attention to α-synuclein inclusions in the substantia nigra and, therefore, degeneration of neuron cell bodies (soma) in the substantia nigra, it is possible that degeneration of neuron axon terminals in the striatum may progress more rapidly than degeneration of nigral cell bodies.…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…8 A reduction of between 14 – 24% of nigral TH neurons or 14 – 34% of striatal dopamine could cause parkinsonian motor manifestations. These values are similar to those reported (about 38% reduction) in low resolution SPECT studies of striatal uptake of a DAT radiotracer in the “normal” side in a group of eight hemiparkinsonian patients 27 and recall that striatal DAT measures strongly correlate with striatal dopamine.…”
Section: Measurement Of Pd Severitymentioning
confidence: 99%